A new semidefined nutrient medium for bacterial susceptibility testing - Reissbrodt, R; Witte, W; Rische, H (Journal of hygiene, epidemiology, microbiology, and immunology, 1983)
A new semidefined nutrient medium for testing of bacterial resistance against chemotherapeutics is described. Nutrients, poor in antagonists, vitamins and ions are balanced. Full effectiveness in view of sensitivity and expression of bacterial resistance mechanisms of all chemotherapeutics tested is guaranteed. The nutrient medium, known under the trade name "Kulturmedium L4 zur Resistenzbestimmung" is comparable with the new recommended international media for this purpose. Beyond it the nutrient medium is useful for genetical investigations and combined with a diagnostic system for selecting different bacteria contained especially resistance properties.
Keywords: Amino Acids; aminokyseliny; antibakteriální látky; Vitamins; Microbial Sensitivity Tests; Bacteria; vitaminy; Culture Media; antibiotická rezistence; Anti-Bacterial Agents; Drug Resistance, Microbial; kultivační média; mikrobiální testy citlivosti